Lit : a memoir - Karr, Mary (Harper, 2009)
The author reveals how, shortly after giving birth to a child she adored, she drank herself into the same numbness that nearly devoured her charismatic but troubled mother, reaching the brink of suicide before a spiritual awakening led her to sobriety.